Evaluation of Malondialdehyde in Type 2 Diabetes Mellitus Patients as Oxidative Stress Markers in Bengkulu Population - Sahidan Sahidan; Raden Sunita; Rachmat Hidayat (HM Publisher, 2020)
Hyperglycemia in Type 2 Diabetes Mellitus (T2DM) can cause individuals to experience oxidative stress conditions, accompanied by a decrease in antioxidant activity in protecting cellular components against the attack of reactive oxygen species (ROS). ROS oxidized lipid components can produce Malondialdehyde (MDA). Evaluation of MDA can be used as a marker Oxidative stress which can indirectly describe the effects of ROS because ROS compounds are reactive. This study aims to determine the analysis of MDA in T2DM subjects at the Sentinel Public Health Center in Bengkulu City in 2017.research Analytic with a case control study design in 40 samples of T2DM subjects (cases) and 40 Non-DM samples (control) were carried out at the Sentinel DM Health Center in Bengkulu City. Data collection used questionnaires, measurements of Body Mass Index, examination of Fasting Blood Glucose and plasma MDA (spectrophotometry). The results of this study there were differences in characteristics (Gender, Age, BMI, Blood Pressure, Fasting Blood Glucose) in subjects with T2DM and Non-T2DM in the Bengkulu City Sentinel Health Center in 2017 (p <0,000). There was a significant difference (p= 0,000) in higher MDA levels in patients with T2DM than non-DM subjects. The MDA frequency distribution in the case was MDNormal (24%) and MDA Normal (6%), whereas in the control was MDA Not Normal (26%) and MDA Normal (44%). There were significant differences in MDA frequency distribution between cases and controls (p= 0,000). The subjects of T2DM had a risk of 6.77 times an increase in MDA levels compared to Non-DMT2 (p= 0.000, OR 6.77 IK 95% 2.44-18.73). The correlation between levels of GDP and MDA was statistically significant (p <0.001) with a positive correlation direction (0.340). The results of this study are expected to be used as a basis for the development of individual therapy in subjects with T2DM in order to prevent the occurrence of complications early on.